Antinociceptive effect of PnTx4(5-5), a peptide from Phoneutria nigriventer spider venom, in rat models and the involvement of glutamatergic system - Oliveira,Camila Franco Batista (2019)
ABSTRACT Background: The venom of Phoneutria nigriventer spider is a source of numerous bioactive substances, including some toxins active in insects. An example is PnTx4(5-5) that shows a high insecticidal activity and no apparent toxicity to mice, although it inhibited NMDA-evoked currents in rat hippocampal neurons. In this work the analgesic activity of PnTx4(5-5) (renamed Γ-ctenitoxin-Pn1a) was investigated. Methods: The antinociceptive activity was evaluated using the paw pressure test in rats, after hyperalgesia induction with intraplantar injection of carrageenan or prostaglandin E2 (PGE2). Results: PnTx4(5-5), subcutaneously injected, was able to reduce the hyperalgesia induced by PGE2 in rat paw, demonstrating a systemic effect. PnTx4(5-5) administered in the plantar surface of the paw caused a peripheral and dose-dependent antinociceptive effect on hyperalgesia induced by carrageenan or PGE2. The hyperalgesic effect observed in these two pain models was completely reversed with 5 µg of PnTx4(5-5). Intraplantar administration of L-glutamate induced hyperalgesic effect that was significantly reverted by 5 μg of PnTx4(5-5) injection in rat paw. Conclusion: The antinociceptive effect for PnTx4(5-5) was demonstrated against different rat pain models, i.e. induced by PGE2, carrageenan or glutamate. We suggest that the antinociceptive effect of PnTx4(5-5) may be related to an inhibitory activity on the glutamatergic system.